Experimental investigation on the effect of asymmetrical sealing on tunnel fire behavior. (January 2016) - Chen, Chang-kun; Zhu, Cong-xiang; Liu, Xuan-ya; Yu, Nian-hao
Highlights: Reduced experiment on tunnel fire behaviors of asymmetrical sealing was conducted. Temperature distribution in the tunnel and radiation near the entrance were tested. Characteristics of fuel burning, smoke flow, hot plume size, etc. were analyzed. Fire shifts to the side with lower ratio as entrances are sealed asymmetrically. Ceiling temperature of different sealing ratios along tunnel was compared. Abstract: Sealing the tunnel entrance is a common tactic for tunnel fire fighting, while it is not easy to seal the two entrances synchronously in actual tunnel fire-fighting process. A set of reduced experiments were then conducted to investigate the effect of asymmetrical sealing of tunnel entrances on tunnel fire behavior and temperature distribution. The data of temperature, radiative heat flux and mass loss rate, etc. were acquired. The results demonstrate that hot smoke region shifts to the side not completely sealed, and burning at the side with less sealing ratio is more violent with higher smoke temperature and longer hot smoke plume. Plume temperature at the tunnel entrance could reach to 300 °C as measured in the experiments and jet flame was observed at the end not completely sealed. These would lead to great danger to fire fighters in actual tunnel fire fighting.